Measurement of coronary bifurcation angle with coronary CT angiography: A phantom study - Givehchi, Sogol; Safari, Mohammad Javad; Tan, Sock Keow; Shah, Mohammad Nazri Md; Sani, Fadhli Mohamed; Raja Aman, Raja Rizal Azman; Sun, Zhonghua; Yeong, Chai Hong; Ng, Kwan Hoong; Wong, Jeannie Hsiu Ding (Elsevier, 2018)
Purpose: Accurate determination of the bifurcation angle and correlation with plaque buildup may lead to the prediction of coronary artery disease (CAD). This work evaluates two techniques to measure bifurcation angles in 3D space using coronary computed tomography angiography (CCTA). Materials and Methods: Nine phantoms were fabricated with different bifurcation angles ranging from 55.3° to 134.5°. General X-ray and CCTA were employed to acquire 2D and 3D images of the bifurcation phantoms, respectively. Multiplanar reformation (MPR) and volume rendering technique (VRT) were used to measure the bifurcation angle between the left anterior descending (LAD) and left circumflex arteries (LCx). The measured angles were compared with the true values to determine the accuracy of each measurement technique. Inter-observer variability was evaluated. The two techniques were further applied on 50 clinical CCTA cases to verify its clinical value. Results: In the phantom setting, the mean absolute differences calculated between the true and measured angles by MPR and VRT were 2.4° ± 2.2° and 3.8° ± 2.9° respectively. Strong correlation was found between the true and measured bifurcation angles. Furthermore, no significant differences were found between the bifurcation angles measured using either technique. In clinical settings, large difference of 12.0° ± 10.6° was found between the two techniques. Conclusion: In the phantom setting, both techniques demonstrated a significant correlation to the true bifurcation angle. Despite the lack of agreement of the two techniques in the clinical context, our findings in phantoms suggest that MPR should be preferred to VRT for the measurement of coronary bifurcation angle by CCTA.